Patala the layers of Eye - basis of all eye disorders in Ayurveda a critical review. - Sharma, Himani; Mehar, Kapil; Tripathi, Ankur; Bavalatti, Narayan; Kundal, Pankaj; Sharma, Swati (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda is a science that is discovery oriented and explore fundamental theory as scientific facts. With time these facts have been illustrated by the founding fathers of Ayurveda. Ayurvedic dogma have elucidated Netra Rachna Sharir and Kriya Sharir in a beautiful descriptive manner, still there is need of exploring the terminologies for proper understanding of pathogenesis of Netra Rogas and their managements so that implementation of Ayurvedic concepts in eye disease can be done. Acharya sushruta elucidated the Netra Sharira into three distinct part called as Mandala, Sandhi and Patala. In this literary research paper we have tried to establish alliance of Netra Patalas according to their anatomical position in eye and pathology.